A critical examination of the concept of education for self-reliance with reference to Swaziland - Vilakati, Alpheus Velamuva (My University, 1993)
In this research report I try zo critically investigate the concept of education for self-reliance, a policy which some African leaders such as Julius Nyere of Tanzania have tried to implement. Amongst other things these African leaders claimed that the education system provided in the 1960's in former African colonies was inadequate and inappropriate for peoples who were still developing. For example Nyerere of Tanzania claimed that graduates of the education system in Tanzania prior to 1967 had the attitude of looking down upon manual skills and manual labour in preference to knowledge appropriate to white-collar jobs. As a result Nyerere launched his policy of education for Self-reliance for Tanzania in 1967. Implicit in Education for self-reliance is the idea of the vocationalisation of education. However, the research report posits that while such an idea is acceptable the concept of education for self-reliance needs careful analysis in order to be a viable notion of any education system. Education for self-reliance as practised hitherto by former African colonies seems to have been biased towards community or national development to the extent of undermining individual development of a person's individuality. Thus this research report focuses on the concepts of individual and community regarding the aims of education with reference to Swaziland. The education system in Tanzania before 1967 is examined in order to provide some case study since Tanzania seems to have been the only country which has formaly put into practise the policy of education for self-reliance.
A Research Report submitted to the Faculty of Education, University of the Witwatersrand in partial fulfilment of the degree in of Master of Education at the University of the Witwatersrand, Johannesburg
Keywords: Education -- Swaziland.; Vocational education -- Swaziland; Self-reliance